Pengaruh Cash Flow Audit Report Lag dan Disclosure terhadap Opini Audit Going Concern pada Perusahaan Sektor Energi di Bursa Efek Indonesia (BEI) Periode 2019 - 2023 - Gita Aulia Putri; Suciati Muanifah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
An opini going concern embodies an auditor's judgment regarding a firm's capacity to sustain its commercial activities into the near-term future. This inquiry endeavors to scrutinize the bearing of cash flow, audit report lag, and disclosure on the conferral of an opini going concern. The examination concentrates on corporations in the energy sector recorded on the Indonesia Stock Exchange (IDX) across the 2019–2023 interval. A quantitative method was applied through the use of logistic regresi analysis. This research drew upon secondary data sourced from corporate annual statements. The specimens were chosen via a purposive sampling technique founded on specified requirements. The conclusions demonstrate that, in a simultan fashion, cash flow, audit report lag, and disclosure wield a signifikan impact upon the opini going concern. Nevertheless, in a parsial review, only cash flow displays a signifikan inverse correlation, implying that a greater operating cash flow diminishes the prospect of obtaining an opini going concern. Conversely, audit report lag and disclosure were found to exert no signifikan leverage on this audit judgment.